KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU: STUDI KEPUSTAKAAN PADA PENDIDIKAN RAUDHATUL ATHFAL - Khairun Nisya; Rodhatul Jennah; Hamidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Transformational leadership of madrasah principals plays a strategic role in improving the performance of Raudhatul Athfal (RA) teachers, particularly in addressing the continuously evolving challenges of early childhood education. This article aims to conceptually examine how the transformational leadership of madrasah principals contributes to the improvement of RA teachers’ performance within the context of Raudhatul Athfal education. The method employed in this study is library research, which involves reviewing various literature sources such as books, scholarly articles, and academic journals relevant to transformational leadership, madrasah management, and teacher performance. The findings indicate that transformational leadership, characterized by an inspirational vision, motivation, role modeling, and teacher empowerment, is able to enhance teachers’ professionalism, work commitment, and the quality of learning in RA. Therefore, transformational leadership of madrasah principals is an important factor in achieving sustainable improvement in the quality of RA education, particularly within the framework of Islamic education at the early childhood education level.